2015
DOI: 10.1002/jcc.23857
|View full text |Cite
|
Sign up to set email alerts
|

Dividing a complex reaction involving a hypervalent iodine reagent into three limiting mechanisms by ab initio molecular dynamics

Abstract: The electrophilic N-trifluoromethylation of MeCN with a hypervalent iodine reagent to form a nitrilium ion, that is rapidly trapped by an azole nucleophile, is thought to occur via reductive elimination (RE). A recent study showed that, depending on the solvent representation, the S(N)2 is favoured to a different extent over the RE. However, there is a discriminative solvent effect present, which calls for a statistical mechanics approach to fully account for the entropic contributions. In this study, we perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 32 publications
2
40
0
Order By: Relevance
“…This functional group displays ahigh degree of chemoselectivity,a sd emonstrated, for example, by an octapeptide derived from Sandostatin, [18,19] or by co-enzymeA. [21][22][23][24][25][26][27][28][29][30] We previously investigatedt he electronica nd structural properties leadingt o the distinct reactivity of reagent 1 as well as polar mechanistic details in combination with N-a nd S-nucleophiles. [21][22][23][24][25][26][27][28][29][30] We previously investigatedt he electronica nd structural properties leadingt o the distinct reactivity of reagent 1 as well as polar mechanistic details in combination with N-a nd S-nucleophiles.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…This functional group displays ahigh degree of chemoselectivity,a sd emonstrated, for example, by an octapeptide derived from Sandostatin, [18,19] or by co-enzymeA. [21][22][23][24][25][26][27][28][29][30] We previously investigatedt he electronica nd structural properties leadingt o the distinct reactivity of reagent 1 as well as polar mechanistic details in combination with N-a nd S-nucleophiles. [21][22][23][24][25][26][27][28][29][30] We previously investigatedt he electronica nd structural properties leadingt o the distinct reactivity of reagent 1 as well as polar mechanistic details in combination with N-a nd S-nucleophiles.…”
Section: Introductionmentioning
confidence: 99%
“…[20] Although the chemistry of iodanes is well established,o nly recent computational studies revealed the mechanistic versatility of l 3 -iodanes, reminiscent of that of transition metals. [24,25,30] Thus, the activation of reagent 1 by protonation is essential. [24,25,30] Thus, the activation of reagent 1 by protonation is essential.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations